Wo manchmal die Gebeine bleichen - Żuchowski, Tadeusz (Artium Quaestiones, 2018)
The status of cemeteries in European culture is unique. Tombs with inscriptions informing about the names of the buried are peculiar examples of historical documents which persuasively illustrate the history of a given region by revealing the truth about the nationality, religious beliefs, and social status of the buried. Thus, cemeteries become unique reservoirs of memory, sometimes turning into objects of ideologically biased interest and even destruction. That was the case of the Protestant cemeteries in Poland which suffered as a result of historical ideologization affecting the regions formerly populated by Germans. A metaphorical account of that process can be found in The Call of the Toad, a novel by Günter Grass. However, the problem is much more complicated. Since the 19th century changes in urban planning of European cities resulted in transforming cemeteries into parks. Various developments of this kind can be observed in Poznań, where till 1939 cemeteries were connected to particular confessions, and, with an exception of the garrison cemetery, there were no burying grounds open to all. The cemeteries which belonged to parishes and communities were taken over by the city and gradually transformed into parks, except the historic ones (the Roman Catholic cemetery on Wzgórze Św. Wojciecha, the Protestant Holy Cross cemetery on Ogrodowa St., and the Jewish cemetery on Głogowska St.). Such changes required a proper waiting period from the moment of the burying ground’s closing to its final disappearance. Fifty years after the last burial a cemetery could be officially taken over by the city. Transformations which began at the beginning of the 20th century were continued in the 1930s, to be completed in the 1950s. Under the Nazi occupation, the decrees of the administrator of the Warthegau made it possible for the city to take over the confessional cemeteries (Roman Catholic, Jewish, and Protestant). Those regulations remained valid after World War II. The City Council took over Protestant and Jewish cemeteries, and removed some Roman Catholic ones. Some of them have been transformed into parks. Consequently, all the Protestant and Jewish cemeteries, and some Roman Catholic ones, disappeared from the city map in 1945–1973. Most of them have been changed into parks and squares. The Protestant cemeteries were considered German and the parks located on such areas received significant names, e.g., Victory Park, Partisans’ Park, etc. Cemeteries were often being closed in a hurry and until today on some construction sites contractors can find human bones.